Mind Mapping Technique In Vocabulary Teaching And Learning Context: A Systematic Literature Review - Muh. Syukur; Citra Prasiska Puspita Tohamba; Faridawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This systematic literature review aims to synthesize previous research findings to see how is mind mapping can be effective in vocabulary learning. This systematic literature review was conducted on research articles related to the use of mind mapping in teaching and learning vocabulary, using various databases such as Google Scholar, Science Direct, Eric, and Research Gate databases to conduct the search. The search was conducted on national and international articles published in the last 5 years (2020-2024). Of the 206 articles found in the search, 7 articles were selected to be the subject of the systematic review based on keywords and their limitations. The PRISMA 2020 flowchart was used in the article selection process. The findings of this study, it was found that mind mapping has an effective impact on vocabulary learning because: (1). Mind mapping has an effect on short-term and long-term vocabulary memory, (2). Mind mapping can increase students' learning motivation, (3). Mind mapping increases the willingness to learn independently, (4). Mind mapping helps students to be able to use both their right and left brain, (5). Mind mapping increases students' willingness to communicate (WTC).